Modern approaches to modeling user requirements on resource and task allocation in hierarchical computational grids - Kołodziej, Joanna; Xhafa, Fatos (Zielona Góra: Uniwersytet Zielonogórski)
Tasks scheduling and resource allocation are among crucial issues in any large scale distributed system, including Computational Grids (CGs). These issues are commonly investigated using traditional computational models and resolution methods that yield near-optimal scheduling strategies. One drawback of such approaches is that they cannot effectively tackle the complex nature of CGs. On the one hand, such systems account for many administrative domains with their own access policies, user privileges, etc. On the other, CGs have hierarchical nature and therefore any computational model should be able to effectively express the hierarchical architecture in the optimization model.
Keywords: computational grids; scheduling; non-cooperative games; user behavior; security; meta-heuristics